Harmonizing multisite data with the ComBat method for enhanced Parkinson’s disease diagnosis via DAT-SPECT - Wakasugi, Noritaka; Takano, Harumasa; Abe, Mitsunari; Sawamoto, Nobukatsu; Murai, Toshiya; Mizuno, Toshiki; Matsuoka, Teruyuki; Yamakuni, Ryo; Yabe, Hirooki; Matsuda, Hiroshi; Hanakawa, Takashi; , Parkinson’s; et al. (Frontiers in Neurology, 2024)
Background: Dopamine transporter single-photon emission computed tomography (DAT-SPECT) is a crucial tool for evaluating patients with Parkinson's disease (PD). However, its implication is limited by inter-site variability in large multisite clinical trials. To overcome the limitation, a conventional prospective correction method employs linear regression with phantom scanning, which is effective yet available only in a prospective manner. An alternative, although relatively underexplored, involves retrospective modeling using a statistical method known as the 'combatting batch effects when combining batches of gene expression microarray data (ComBat)'. Methods: We analyzed DAT-SPECT specific binding ratios (SBRs) derived from 72 healthy older adults and 81 patients with PD registered in four clinical sites. We applied both the prospective correction and the retrospective ComBat correction to the original SBRs. Next, we compared the performance of the original and two corrected SBRs to differentiate the PD patients from the healthy controls. Diagnostic accuracy was assessed using the area under the receiver operating characteristic curve (AUC-ROC). Results: The original SBRs were 6.13±1.54 (mean±standard deviation) and 2.03±1.41 in the control and PD groups, respectively. After the prospective correction, the mean SBRs were 6.52±1.06 and 2.40±0.99 in the control and PD groups, respectively. After the retrospective ComBat correction, the SBRs were 5.25±0.89 and 2.01±0.73 in the control and PD groups, respectively, resulting in substantial changes in mean values with fewer variances. The original SBRs demonstrated fair performance in differentiating PD from controls (Hedge's g=2.76; AUC-ROC=0.936). Both correction methods improved discrimination performance. The ComBat-corrected SBR demonstrated comparable performance (g=3.99 and AUC-ROC=0.987) to the prospectively corrected SBR (g= 4.32 and AUC-ROC 0.992) for discrimination. Conclusion: Although we confirmed that SBRs fairly discriminated PD from healthy older adults without any correction, the correction methods improved their discrimination performance in a multisite setting. Our results support the utility of harmonization methods with ComBat for consolidating SBR-based diagnosis or stratification of PD in multisite studies. Nonetheless, given substantial changes in the mean values of ComBat-corrected SBRs, caution is advised when interpreting them.